2018
DOI: 10.3906/sag-1709-144
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment outcomes in community-acquired pneumonia

Abstract: Background/aim: The optimal empiric antibiotic regimen for patients with community-acquired pneumonia (CAP) remains unclear. This study aimed to evaluate the clinical cure rate, mortality, and length of stay among patients hospitalized with communityacquired pneumonia in nonintensive care unit (ICU) wards and treated with a β-lactam, β-lactam and macrolide combination, or a fluoroquinolone. Materials and methods:This prospective cohort study was performed using standardized web-based database sheets from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Menendez et al has reported leucopenia as a predictive factor for TF [5]. Higher leucocytosis is defined as a predictive for TF [17,21]. Gündüz et al's study found no difference in CRP levels at admission between TF and TS groups [13].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Menendez et al has reported leucopenia as a predictive factor for TF [5]. Higher leucocytosis is defined as a predictive for TF [17,21]. Gündüz et al's study found no difference in CRP levels at admission between TF and TS groups [13].…”
Section: Discussionmentioning
confidence: 97%
“…Gündüz et al's study found no difference in CRP levels at admission between TF and TS groups [13]. In contrast, higher CRP levels are shown to be as a demonstrator of deterioration with CAP in more severe and more risky patients [21,22]. Higher PSI score has been found to be the only significant parameter in the multicenter study of Gunduz et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…20 Similarly, in our study, NLR was found higher in IRFG, 21,22 In several studies, no signifi cant diff erence was observed between the use of macrolides, beta lactam antibiotics and fl uoroquinolones in the antibiotic regimen in CAP patients. 23 In our study, moxifl oxacin antibiotics that belong to fl uoroquinolone are detected to be widely used in pneumonia.…”
Section: Discussionmentioning
confidence: 80%
“…The following answers were proposed: the use of ampicillin/ oxacillin (Ampiox); the use of ciprofloxacin; the use of cefazolin; the use of ampicillin per os; the use of respiratory fluoroquinolones in patients without risk factors and a "not sure" option. According to the clinical guidelines (Chuchalin et al 2010), all the options referred to an erroneous strategy in managing non-severe CAP patients: the use of ampicillin per os is accompanied by low bioavailability (40.0%) in comparison with amoxicillin (75-93.0%); cefazolin has a low activity against pneumococci, as well as the absence of clinically significant activity against H. influenzae; ciprofloxacin is low-active against S. pneumoniae and M. pneumonia; it is inappropriate to prescribe respiratory fluoroquinolones as drugs to patients without risk factors; ampicillin/oxacillin (Ampiox) should not be used in medical practice because of an irrational combination of antibiotics (Çilli et al 2018;Cillóniz et al 2018). The majority of students gave an incomplete correct answer -90.5%, fewer than 1.0% of the respondents were able to give the correct answer, and 9.3% of the respondents gave a wrong answer.…”
Section: Resultsmentioning
confidence: 99%